Evaluating the willingness to pay for improved water supply by poultry and non-poultry farmers in Wakiso District, Uganda - Karuiahe, Selma (University of Pretoria, 2022)
Mini Dissertation (MPhil (Agricultural Economics))--University of Pretoria, 2021.